2019
DOI: 10.1080/20013078.2019.1588555
|View full text |Cite
|
Sign up to set email alerts
|

Imaging flow cytometry facilitates multiparametric characterization of extracellular vesicles in malignant brain tumours

Abstract: Lamszus (2019) Imaging flow cytometry facilitates multiparametric characterization of extracellular vesicles in malignant brain tumours,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
118
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 54 publications
9
118
0
Order By: Relevance
“…By using these eGFP‐labelled EVs as biological reference material, we further show that IFCM can be used to analyse sEVs in EV‐containing samples without any preparation, even with cells being present. Single sEVs can be labelled with fluorophore‐conjugated antibodies, which surely is of high interest for studies aiming at biomarker discovery, as we have further elaborated in our approach to specifically detect glioblastoma derived EVs [78]. Here, at the example of MSC‐derived CM we demonstrate that the ISX facilitates robust multicolour analyses of sEVs without the prior need for EV isolation or enrichment.…”
Section: Discussionmentioning
confidence: 95%
“…By using these eGFP‐labelled EVs as biological reference material, we further show that IFCM can be used to analyse sEVs in EV‐containing samples without any preparation, even with cells being present. Single sEVs can be labelled with fluorophore‐conjugated antibodies, which surely is of high interest for studies aiming at biomarker discovery, as we have further elaborated in our approach to specifically detect glioblastoma derived EVs [78]. Here, at the example of MSC‐derived CM we demonstrate that the ISX facilitates robust multicolour analyses of sEVs without the prior need for EV isolation or enrichment.…”
Section: Discussionmentioning
confidence: 95%
“…Ricklefs et al [49] previously showed that circulating EV concentrations in GBM patients are elevated. Tumor-specific EVs were detected in a syngeneic mouse tumor model [49].…”
Section: Evs In Glioblastomamentioning
confidence: 97%
“…Ricklefs et al [49] previously showed that circulating EV concentrations in GBM patients are elevated. Tumor-specific EVs were detected in a syngeneic mouse tumor model [49]. Osti et al [35] ( Table 1) analyzed plasma EVs (microvesicles) in preoperative GBM samples.…”
Section: Evs In Glioblastomamentioning
confidence: 97%
“…Other potential limitations may be that the fluorescence intensity is dependent on protein expression level, the efficiency of EV membrane labeling, and excitation strength of the light source (42). However, IFC is sensitive, detecting low fluorescence intensity with accurate visualization of CD63-GFP particles at the 100 nm range (27,31).…”
Section: Ev In Vitro Uptake Standardization Processmentioning
confidence: 99%
“…Previously, researchers have used standard flow cytometry along with various forms of low throughput microscopy including confocal microscopy to analyze EV uptake (25)(26)(27). However, these technologies have several limitations.…”
mentioning
confidence: 99%